Peran BMT Syari’ah Jaya Abadi dalam Peningkatan Pendapatan Usaha Mikro di Kecamatan Giri Mulya Kabuapaten Bengkulu Utara - Ade Riang; Desi Isnaini; Amimah Oktarina (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2023)
The purpose of this study 1) to determine the role of BMT Syari'ah Jaya Abadi in increasing micro business income in Giri Mulya District, North Bengkulu Regency. 2) To find out what are the obstacles of BMT Syari'ah Jaya Abadi in increasing micro business income in Giri Mulya District, North Bengkulu Regency. The approach used in this research is non-participant qualitative and descriptive analysis method. Data was collected through direct explanations from the head of BMT Syari'ah Jaya Abadi, Managers and Customers of Syari'ah Jaya Abadi as the unit of analysis for this research. The results of this study indicate that 1) The role of BMT Syari'ah Jaya Abadi, Giri Mulya District, North Bengkulu Regency, namely first, fostering an entrepreneurial spirit in the community. Second, being able to suppress the practice of usury in the midst of society. Third, improve people's welfare. 2) The obstacles to BMT Syari'ah Jaya Abadi, Giri Mulya District, North Bengkulu Regency, namely the delay in returning customers' capital money and the large number of customers who have not been able to manage their finances.